Insights on the molecular interactions of tapioca starch with xylitol, Arabic gum, and pectin and their effects on its pasting properties and retrogradation kinetics - Rolandelli, Guido (2025)
Fil: Rolandelli, Guido. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina